POLITICAL COMMUNICATION STRATEGY LEGISLATIVE CANDIDATES CAMPAIGN IN SOUTWEST ACEH - Ediyan Saputra (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2018)
Some candidates must already build up its image ahead of time in the process of seeking support and gain much public sympathy. Politicians, as a political communicator, to be able to make an effective political communication with the masses in order to build an image (images buildings), restore the image (image recovery), and maintaining the image (maintenance of image). In an occasion democratic party that is Election legislature that had elapsed, the authors wanted to examine and analyze return strategies Legislative Candidates who have been successful in grabbing power, especially candidates DPRK, political movements and the forces of what he achieved before the democratic party took place, on that occasion the author examines this issue in the province of Aceh Regency of Southwest Aceh District of Manggeng. In this paper, entitled "Political Communication Strategies candidates in the campaign in Southwest Aceh". The author wants to analyze the communication strategies of political candidates Manggeng in the sub-district just ahead Legislative Candidates and what factors influence people's behavior towards lection Manggeng candidates. This paper uses methodology includes a variety of methods and approaches used to achieve the goals and objectives of the study. Planning research methodology should be done regularly. In this study, using a qualitative descriptive study based locally by interviewing respondents, Candidate Legislative and local communities. Analysis of these results ranging from Manggeng Legislative Candidates Political Communication Strategies, Public needs candidates in the campaign, and the phenomenon of the field during the campaign. Most of the communication strategy in the sub-district Manggeng Political candidates have leverage in persuading or influencing the community in its campaign, the form of strategy do the candidates are using billboards, make political meetings with the community, and help distribute the infrastructure according to the needs of society Manggeng. To improve the livelihoods of fellow Muslims would be wonderful in this political strategy we conducted in accordance with good political ethics that has been regulated by the State and which has been set by Islam.